Decision Support System For Determining Raskin Assistance Using The Electre Method - Agam Padly; M. Fakhriza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The problem of poverty remains the biggest problem to date. The government, as the responsible for this problem, always tries its best to solve this problem. One of the solutions that the government has provided in this regard is to launch social programs such as the Raskin program. Raskin as a program has many benefits such as food security and social protection for poor households. This research attempts to support the government in this program, by developing a program to determine the right target of Raskin beneficiaries. This program is built on a web base by adopting a decision support system using the electre method. This method is a multi-criteria method based on ranking. Based on the results of calculations using this program, it is concluded that the best alternatives are Dea, Fadil and Fitri